Possible Use of a Safety-Valve with a Foley Catheter During Catheterisation of Male Spinal Cord Injury Patients for Prevention of Urethral Trauma Caused by Inflation of the Catheter Balloon in the Urethra - Subramanian V; Soni BM (Medical Devices: Evidence and Research, 2023)
Vaidyanathan Subramanian, Bakulesh Madhusudan Soni Regional Spinal Injuries Centre, Southport and Formby District General Hospital, Town Lane, Southport, Merseyside, PR8 6PN, UKCorrespondence: Vaidyanathan Subramanian, Email subramanian.vaidyanathan@nhs.netAbstract: We used a safety-valve (Trans-Urethral Catheterisation Safety Valve, Class Medical, Limerick, Ireland) to prevent urethral trauma due to inflation of the anchoring balloon in the urethra during catheterisation of male spinal cord injury patients in a spinal unit. The safety-valve is attached to the balloon channel of a Foley catheter. If the balloon is inflated when it is in the urethra, the pressure valve is activated. Any fluid pushed into the balloon channel leaks out and balloon inflation stops, indicating that the balloon is not inside the bladder. The safety-valve was used in 44 catheterisations. There was leakage of water during three catheterisations. In the first case, the health professional did not inflate and deflate the balloon prior to its use. This “pre-valve inflation” step overcomes the baseline resistance pressure of the balloon and prevents fluid leaking from the valve when the catheter is in the correct position. In the second instance, the valve was found to be defective. In the third case, the catheter had been misplaced; it was removed and repositioned; there was no leakage of water during inflation of the balloon. In one out of 44 catheterisations, the catheter had been misplaced; leakage of water from the safety-valve stopped inflation of the balloon and prevented iatrogenic urethral trauma. The safety-valve may be used during catheterisation of male patients in the spinal unit to prevent urethral trauma caused by inflation of the balloon of Foley catheter in the urethra. However, health professionals should remember the few shortcomings of the catheter safety-valve.Keywords: spinal cord injury, urethral catheterisation, patients, iatrogenic, catheter, urethra